PEMBUATAN SISTEM INFORMASI KEANGGOTAAN PADA TOKO RITEL "X" - Andre Dwi Cahya; Monica Widiasri; Daniel Soesanto (CALYPTRA, 2018)
Retail stores "X" is a network of stores engaged in retailing. Currently, the retail store "X" has a membership information system to store and manage the data of customers who are registered as members. However, the current membership information system less reliable. Some administrative processes also run less efficiently because of the involvement of the outside of the system. Information obtained from the system less assist management in making decisions. Data derived from the system Point of Sales (POS) is inputted manually, so that the resulting data is not up-to-date, and allow for errors in data entry. The level of system security is still lacking, and system development is hard to do. The new membership information system created by the old system of membership information. Creation of new systems is done by using a framework to address the safety and development of the system. The new membership system that does not use the card, but uses a mobile phone number for verification purposes. New reports were made to add the necessary information management. Some features updated and added so that the process can be more efficient administration. In addition, web application service designed to facilitate the exchange of data between the POS system and membership information system. Based on trial results, it was concluded that the information system of new members can be more effective and efficient and have a better security system.